Inside the black box : a simple guide to quantitative and high frequency trading - Narang, Rishi K, 1974- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
New edition of book that demystifies quant and algo trading In this updated edition of his bestselling book, Rishi K Narang offers in a straightforward, nontechnical style-supplemented by real-world examples and informative anecdotes-a reliable resource takes you on a detailed tour through the black box. He skillfully sheds light upon the work that quants do, lifting the veil of mystery around quantitative trading and allowing anyone interested in doing so to understand quants and their strategies. This new edition includes information on High Frequency Trading. Offers an updat.
What Constitutes a "Good" Model?Overfitting; Out-of-Sample Testing; Assumptions of Testing; Summary; Note; Part Three A Practical Guide for Investors in Quantitative Strategies; Chapter 10 Risks Inherent to Quant Strategies; Model Risk; Inapplicability of Modeling; Model Misspecification; Implementation Errors; Regime Change Risk; Exogenous Shock Risk; Contagion, or Common Investor, Risk; How Quants Monitor Risk; Summary; Notes; Chapter 11 Criticisms of Quant Trading; Trading Is an Art, Not a Science; Quants Cause More Market Volatility by Underestimating Risk; The Market Turmoil of 2008.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Portfolio management -- Mathematical models; Investment analysis -- Mathematical models; Stocks -- Mathematical models; Portfolio management -- Mathematical models; Investment analysis -- Mathematical models; Stocks -- Mathematical models; BUSINESS & ECONOMICS -- Investments & Securities -- General; Investment analysis -- Mathematical models; Portfolio management -- Mathematical models; Stocks -- Mathematical models; Portfolio management / Mathematical models; Investment analysis / Mathematical models; Stocks / Mathematical models; Electronic books; Electronic books